Laparoscopic Approach in Surgical Staging of Endometrial Cancer - Mariana Mouraz; Cátia Sofia Ferreira; Sónia Gonçalves; Nuno Nogueira Martins; Francisco Nogueira Martins (Revista Brasileira de Ginecologia e Obstetrícia, 2019)
Abstract Objective To compare laparoscopy with laparotomy for surgical staging of endometrial cancer. Methods A cohort of women with preoperative diagnosis of endometrial cancer who underwent surgical staging was retrospectively evaluated. The main study end points were: morbidity and mortality, hospital length of stay, perioperative adverse events and recurrence rate. Data analysis was performed with the software SPSS v25 (IBM Corp., Armonk, NY, USA), categorical variables using a Chi-square and Fisher test, and continuous variables using the Student t-test. Results Atotal of 162 patientswere analyzed. 138 patientsmet the inclusion criteria, 41of whom underwent staging by laparoscopy and 97 by laparotomy. Conversions from laparoscopy to laparotomy happened in 2 patients (4.9%) and were secondary to technical difficulties and poor exposure. Laparoscopy had fewer postoperative adverse events when compared with laparotomy (7.3% vs 23.7%, respectively; p = 0.005), but similar rates of intraoperative complications, despite having a significantly longer operative time (median, 175 vs 130 minutes, respectively; p < 0.001). Hospital stay was significantly lower in laparoscopy versus laparotomy patients (median, 3 vs 7 days, respectively; p < 0.001). No difference in recurrence or mortality rates were observed. Conclusion Laparoscopic surgical staging for endometrial cancer is feasible and safe. Patients have lower postoperative complication rates and shorter hospital stays when compared with the approach by laparotomy.